Molecular Subtyping for Predicting Pathological Upstaging and Survival Outcomes in Clinically Organ-confined Bladder Cancer Patients Undergoing Radical Cystectomy - Joep J. de Jong; James A. Proudfoot; Siamak Daneshmand; Robert S. Svatek; Vikram Narayan; Elai Davicioni; Shreyas Joshi; Aaron Dahmen; Roger Li; Brant A. Inman; Paras Shah; Iftach Chaplin; et al. (European Urology Open Science)
Background and objective: Many patients with bladder cancer are understaged. Previous work revealed that molecular subtyping using Decipher Bladder improves clinical staging. This multicenter validation study evaluated Decipher Bladder for upstaging in patients who underwent radical cystectomy (RC) without neoadjuvant therapy. Methods: The Decipher Bladder genomic subtyping classifier (GSC; Veracyte, San Diego, CA, USA) was performed on bladder tumor specimens from patients with high-grade, clinically organ-confined (cTa-T2N0M0) urothelial carcinoma who subsequently underwent RC without neoadjuvant chemotherapy. The primary endpoint was pathological upstaging to non–organ-confined (NOC) disease (pT3+ and/or N+) at RC. The secondary endpoints included overall survival (OS) and pathological upstaging to MIBC+ disease (pT2+ and/or N+) at RC within clinically non–muscle-invasive bladder cancer (cNMIBC) cases. Key findings and limitations: A total of 226 patients (134 cNMIBC [cTa/Tis/T1] and 92 cT2) were analyzed from eight participating institutions. Upstaging to NOC disease was observed in 33% of patients (19% for cNMIBC and 53% for cT2). Molecular subtyping identified 138 luminal and 88 nonluminal tumors. Rates of upstaging to NOC were 41% in nonluminal and 28% in luminal tumors (univariable p = 0.04), which was not independently significant after adjusting for clinical variables. Upstaging to MIBC+ in cNMIBC patients was lower in luminal versus nonluminal tumors (32% vs 51%, multivariable p = 0.03). Patients with nonluminal tumors had worse OS on multivariable analyses (p < 0.05). Limitations include retrospective design and sample size. Conclusions and clinical implications: Luminal tumors represent less aggressive disease, reflected by lower rates of pathological upstaging and favorable OS with RC compared with nonluminal tumors. Patient summary: Molecular subtyping suggests that in clinically non–muscle-invasive bladder cancer, luminal tumors harbor less aggressive disease, as reflected by lower rates of pathological upstaging to muscle-invasive disease and favorable outcomes with radical cystectomy, in comparison with nonluminal bladder cancer.